"Shunkan on Devil Island": Domesticating Political Exile in the Japanese Puppet Play “Heike nōgyo no shima” (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
This essay discusses the scene entitled Shunkan on Devil Island from Chikamatsu Monzaemon’s early modern puppet play  The Heike on the Island of Women  as a commentary on social and political strictures of the early modern Tokugawa shogunate, which increasingly regulated social and commercial life as it sought to maintain control of the burgeoning cities of Edo and Osaka in the early 1700s. The play is loosely based on the medieval epic war tale Tale of the Heike (Heike monogatari), a beloved and foundational text that has found numerous afterlives in Japan’s theatrical, narrative and cinematic traditions. Shunkan on Devil Island  refashions the Heike’s story of the Buddhist prelate Shunkan (banished to Devil Island following a botched coup attempt) as a specifically early modern tale by introducing a female character, Chidori, who becomes the wife of one of Shunkan’s two fellow male exiles and therefore a member of the "family" that they, as aristocrats banished to a distant island, create. Through exploring the idea of family relations on the remote Kigaigashima, Chikamatsu recasts the well-known tale of Shunkan on Devil Island to create a utopic staged space that comments on the oppressiveness of the early modern polity experienced acutely by the urban audiences of the early 18th century.
Keywords: ningyō jōruri; Early modern theatre; Tale of the Heike; Chikamatsu Monzaemon; Shunkan; Japanese puppet theatre; bunraku